The role of lachesis in speech disorders: insights from a homeopathic case study - Dudhwala, Roni; Sanghani, Chandni Harsukhbhai; Rathod, Shivani Kishnakant (International Journal of Contemporary Pediatrics, 2025)
Speech disorders in children range from language delays to articulation issues, affecting their social, academic, and emotional development. Lachesis, a homeopathic remedy derived from bushmaster snake venom, is examined for its potential in treating these disorders. This article explores its benefits, particularly when conventional treatments are inadequate, offering an alternative approach to pediatric speech challenges.